2011
DOI: 10.1097/prs.0b013e318208d0d4
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Complications on Patient Satisfaction in Breast Reconstruction

Abstract: Aesthetic satisfaction after breast reconstruction is lower in patients developing a complication, older patients, and those receiving an implant reconstruction. Furthermore, patients with a prophylactic mastectomy are more likely than those with a therapeutic mastectomy to be dissatisfied when complications arise. These relationships are important, as measures to improve quality and decrease complications can directly improve patient satisfaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
73
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 143 publications
(84 citation statements)
references
References 28 publications
5
73
1
5
Order By: Relevance
“…Reconstruction failure was significantly associated with a lower general satisfaction in patients with tissue expander (TE) and permanent implant (PI) replacement [16]; moreover, a postoperative complication was a particularly important indicator of dissatisfaction in patients with reconstruction [17]. Colakoglu [18] reported that patients with breast reconstruction who developed complications had a lower esthetic satisfaction compared with patients who did not. Therefore, it is important to prevent complications from impairing the satisfaction of patients with breast reconstructions.…”
Section: Introductionmentioning
confidence: 98%
“…Reconstruction failure was significantly associated with a lower general satisfaction in patients with tissue expander (TE) and permanent implant (PI) replacement [16]; moreover, a postoperative complication was a particularly important indicator of dissatisfaction in patients with reconstruction [17]. Colakoglu [18] reported that patients with breast reconstruction who developed complications had a lower esthetic satisfaction compared with patients who did not. Therefore, it is important to prevent complications from impairing the satisfaction of patients with breast reconstructions.…”
Section: Introductionmentioning
confidence: 98%
“…7 In addition to the psychological burden patients face, this negative impact on patient satisfaction has consequences for the hospital. Patient satisfaction is one metric that Medicare uses in the Hospital Inpatient Quality Reporting program, which financially incentivizes hospitals to report quality measures and makes these results public.…”
mentioning
confidence: 99%
“…Aesthetic satisfaction with implant breast reconstruction seems to decrease with time. 28,29 Clough found a significant deterioration in 46 percent of cases in 5 years. Capsular contracture was the main factor that contributed to this.…”
Section: Discussionmentioning
confidence: 96%